MULTIMODAL STUDY OF GERIATRIC MILD TRAUMATIC BRAIN INJURY USING COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE IMAGING. (11th November 2018) - Irimia, A; Maher, A; Chowdhury, N; Rostowsky, K; Law, M
Abstract: In recent decades, the joint use of computed tomography (CT) and magnetic resonance imaging (MRI) to study geriatric mild traumatic brain injury (mTBI) has increased considerably. Although MRI is the gold standard for the noninvasive evaluation of white matter (WM) and gray matter (GM) volumes in the living human brain, CT continues to be used widely during treatment of geriatric mTBI, particularly when MRI is unavailable or contraindicated. Furthermore, in clinical settings, CT scans are frequently acquired from geriatric mTBI patients even though MRI scans are not. Partly for this reason, there has been renewed interest in the development of CT-only approaches to the calculation of brain structure changes after geriatric mTBI. In this study, we introduce a novel, CT-only brain segmentation method and validate it using both MRI and CT volumes acquired from ten geriatric mTBI volunteers (age: µ = 65 yrs; σ = 7 yrs). Segmentation accuracy is quantified using the Sørensen-Dice coefficient (SDC), a robust measure of inter-modality tissue classification agreement between CT and MRI. Across all cases, the mean and standard deviation of the SCD is found to be 85.5% ± 4.6% for WM and 86.7% ± 5.6% for GM, indicating excellent ability to calculate GM/WM volumes from CT in geriatric mTBI patients. Since mTBI has higher incidence after age 65 than in any other adult age group, our contribution is important because it broadens the ability to integrate CT-based findings into research studies of geriatric mTBI and of its effects upon brain aging and neurodegeneration.